2015
DOI: 10.2214/ajr.15.14668
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Impact of Risk-Based Screening Mammography in Women 40–49 Years Old

Abstract: Very strong family history and extremely dense breast tissue were absent in most 40- to 49-year-old women with breast cancer detected at screening mammography. These cancers were frequently invasive (often with nodal metastases) and treatable (hormone receptor positive). Reducing the number of women to be screened in this age group by using this risk-based approach would reduce the number of screen-detected cancers by more than 75%, thereby precluding the benefit of mortality reduction. Even using a risk-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Also, they have proposed risk-based screening, such as selective screening of women 40 to 49 years old who are at increased risk of breast cancer, as a means of improving the benefit-to-risk ratio using a meta-analysis. However, a recent retrospective study suggested that 88% and 86% of women with screening-detected breast cancer did not have a very strong family history of breast cancer or extremely dense breast tissue, respectively (Price et al, 2015). Among patients with screening-detected malignancies, 76% did not have a very strong family history or extremely dense breasts (Ray et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Also, they have proposed risk-based screening, such as selective screening of women 40 to 49 years old who are at increased risk of breast cancer, as a means of improving the benefit-to-risk ratio using a meta-analysis. However, a recent retrospective study suggested that 88% and 86% of women with screening-detected breast cancer did not have a very strong family history of breast cancer or extremely dense breast tissue, respectively (Price et al, 2015). Among patients with screening-detected malignancies, 76% did not have a very strong family history or extremely dense breasts (Ray et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…• T1-weighted 3D images, acquired using a VIBE sequence with fat saturation and a nominal resolution of (0.759 9 0.759 9 0.900) mm 3 , as routinely used in clinical dynamic contrast-enhanced MRI protocols for the breast;…”
Section: A2 Mr Imagingmentioning
confidence: 99%
“…Women with more than 75% density have a fourfold or higher risk of breast cancer compared to those with less than 5% . More intensive screening for women with high mammographic density has been proposed but remains controversial …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk prediction models designed to personalize mammography screening include personal and familial risk factors (9–11), which have been validated in case-control data (12) but less frequently in screening populations (13). A substantial number of women diagnosed with breast cancer do not exhibit breast cancer risk factors (14).…”
mentioning
confidence: 99%